Morphology and molecular phylogeny of a new ciliate, Hemiurosomoida sinica sp. nov. (Ciliophora, Hypotrichia) - Han, Haifeng; Xue, Xiaojin; Zhang, Zhisheng; Shao, Chen (Zootaxa, 2026)
The study investigates the morphology and phylogenetic position of a hypotrichous ciliate, Hemiurosomoida sinica sp. nov. The new species is distinguished from related species by body size and shape, number of macronuclear nodules and caudal cirri, the presence and arrangement of cortical granules, patterns of ventral and dorsal ciliature, as well as the pattern of endoral and paroral membranes. Phylogenetic analyses based on small subunit ribosomal DNA (SSU rDNA) sequences, using both maximum likelihood and Bayesian inference methods, revealed that Hemiurosomoida sinica sp. nov. is positioned within the non-monophyletic Hemiurosomoida clade and exhibits a strong phylogenetic affinity with Hemiurosomoida warreni.